Visual phenomenology in schizophrenia and post-traumatic stress disorder: an exploratory study. Issue 4 (25th July 2022) - Wearne, Deborah; Ayalde, Jeremiah; Curtis, Guy; Gopisetty, Aarethi; Banerjee, Amit; Melvill-Smith, Peter; Orr, Kenneth; Rajanthiran, Leon; Waters, Flavie
Abstract : Background: Visual experiences such as hallucinations are commonly reported by people with psychosis, psychological trauma and dissociative states, although questions remain about their similarities and differences. For diagnostic and therapeutic purposes, clinical research must better delineate and compare the characteristics of these experiences in post-traumatic stress disorder (PTSD) and in schizophrenia. Aims: To compare visual phenomena and dissociation in participants with a primary psychotic illness and those with a trauma diagnosis. Method: A quantitative group design study comparing visual phenomena in three participant groups who also have a history of hearing voices: schizophrenia and no trauma history ( n = 19), PTSD with dissociation ( n = 17) and comorbid schizophrenia and PTSD ( n = 20). Validated clinical measures included the North-East Visual Hallucination Interview, PTSD Symptoms Scale Interview, Clinician Administered Dissociative States Scale, Psychotic Symptoms Rating Scales and Positive and Negative Syndrome Scale. Results: There was a remarkable similarity in visual experiences, including rates of complex visual hallucinations, between the three diagnostic groups. There were no significant differences in the severity or components of distress surrounding the visual experiences. Dissociation predicted visual hallucination severity for the comorbid schizophrenia and PTSD group, but not for PTSD or schizophrenia alone. Conclusions: Visual experiences in PTSD can include visual hallucinations that are indistinguishable from those experienced in schizophrenia. Multimodal hallucinations are frequently observed in both schizophrenia and PTSD. A model for visual hallucinations in PTSD is suggested, following two separate neurobiological pathways based on distinct responses to trauma.